New-new trade policy - Dan Ciuriak; Beverly Lapham; Robert Wolfe; Terry Collins-Williams; John M. Curtis (Queen's University, Department of Economics, 2011)
When national competitiveness is invoked as a policy objective, trade experts have learned to retort that countries don't trade, firms do. This focus on the importance of the firm in international trade is consistent with the most recent developments in trade theory, but policy needs to catch up. Recognizing the growing anomalies in observed trade patterns relative to traditional models of trade based on national comparative advantage, the new trade theory of the 1980s looked at industries not countries, leading Nobel prize-winner Paul Krugman, a pioneer in this literature, to suggest the need for a new trade policy. Recent work on what some call the new-new trade theory focuses on the trading behaviour of individual firms, making a tight link between trade and productivity. In this paper we demonstrate how focusing on firms should be the foundation for a new-new trade policy, one that creates exciting opportunities for trade and investment promotion strategies, along with the need for much more targeted consultation strategies. We also discuss the implications of the new-new theory for regulatory coordination, and on new ways to cooperate with interlocutors in developing countries on the evolution of 21st century trade policy.
Keywords: F00; F10; F12; F13; 330; New-new Trade Theory; Trade Policy; Außenwirtschaftstheorie; Außenhandelspolitik; Strategisches Management; Neue Außenhandelstheorie